Real-time-dynamics quantum simulation of (1+1)-dimensional lattice QED with Rydberg atoms - Simone Notarnicola; Mario Collura; Simone Montangero (Physical Review Research, 2020)
We show how to implement a Rydberg-atom quantum simulator to study the nonequilibrium dynamics of an Abelian (1+1)-dimensional lattice gauge theory. The implementation locally codifies the degrees of freedom of a Z_{3} gauge field, once the matter field is integrated out by means of the Gauss local symmetries. The quantum simulator scheme is based on currently available technology and thus is scalable to considerable lattice sizes. It allows, within experimentally reachable regimes, us to explore different string dynamics and to infer information about the Schwinger U(1) model.